2015
DOI: 10.1111/bdi.12337
|View full text |Cite
|
Sign up to set email alerts
|

Low unesterified:esterified eicosapentaenoic acid (EPA) plasma concentration ratio is associated with bipolar disorder episodes, and omega‐3 plasma concentrations are altered by treatment

Abstract: Objectives Omega (n)-3 and n-6 polyunsaturated fatty acids (PUFA) are molecular modulators of neurotransmission and inflammation. We hypothesized that plasma concentrations of n-3 PUFA would be lower and of n-6 PUFA higher in subjects with bipolar disorder (BD) compared to healthy controls (HC), and would correlate with symptom severity in subjects with BD, and that effective treatment would correlate with increased n-3 but lower n-6 PUFA levels. Additionally, we explored clinical correlations and group differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 101 publications
2
19
0
Order By: Relevance
“…From the variety of medications that both groups were receiving (see Methods), carriers were more likely to be taking antidepressants than controls (30.4% vs. 6.25%; p < 0.0001); among them, the most common class was the selective serotonin reuptake inhibitors (SSRI; n = 6, including one control). However, no difference in metabolite levels was observed in our study consistent with the lack of differences in PUFA levels between medicated and unmedicated subjects reported by others [56,57], No unmedicated subjects were present in any group, but we did not find that the metabolomics data correlated with the presence of the iatrogenic compounds indicated above or with antidepressants, antipsychotics, or mood stabilizers.…”
Section: Xenobiotics Of Pharmaceutical or Dietary Originsupporting
confidence: 90%
“…From the variety of medications that both groups were receiving (see Methods), carriers were more likely to be taking antidepressants than controls (30.4% vs. 6.25%; p < 0.0001); among them, the most common class was the selective serotonin reuptake inhibitors (SSRI; n = 6, including one control). However, no difference in metabolite levels was observed in our study consistent with the lack of differences in PUFA levels between medicated and unmedicated subjects reported by others [56,57], No unmedicated subjects were present in any group, but we did not find that the metabolomics data correlated with the presence of the iatrogenic compounds indicated above or with antidepressants, antipsychotics, or mood stabilizers.…”
Section: Xenobiotics Of Pharmaceutical or Dietary Originsupporting
confidence: 90%
“…Moreover, similar erythrocyte DHA deficits were observed in studies employing adolescent or adult patients, and studies employing medicated or unmedicated patients. Although plasma fatty acid levels are more variable, it is also worth noting that a prior caseÀcontrol study (28), but not others (6,29,30), similarly observed DHA deficits in plasma from patients with bipolar disorder. The present results suggest that bipolar I disorder is associated with robust and selective erythrocyte DHA deficits, and add to a growing body of evidence implicating omega-3 PUFA deficiency in the pathophysiology of bipolar I disorder.…”
Section: Discussionmentioning
confidence: 86%
“…Additional measures were collected but not used for this analysis. For more detailed report on methods and results of analysis of fatty acid concentrations, please see Saunders, et al 35…”
Section: Participants and Methodsmentioning
confidence: 99%